小角度X射线散射测量 (2024)
一种x射线装置，该x射线装置可以包括被配置为保持样品的底座；x射线源，该x射线源被配置为将x射线束引向样品的第一侧；检测器，该检测器位于样品的第二侧的下游，该检测器被配置为在样品测量时段期间检测已经透射通过样品的x射线的至少一部分；以及x射线强度检测器，该x射线强度检测器在射束强度监控时段期间定位在位于x射线源与样品的第一侧之间的测量位置处，以便检测x射线束到达样品之前的x射线束的至少一部分。 An x-ray apparatus, that may include a mount that is configured to hold a sample; an x-ray source, that is configured to direct an x-ray beam toward a first side of the sample; a detector, positioned downstream to a second side of the sample, the detector is configured to detect, during a sample measurement period, at least a part of x-rays that have been transmitted through the sample; and an x-ray intensity detector that is positioned, during a beam intensity monitoring period at a measurement position that is located between the x-ray source and the first side of the sample, so as to detect at least a part of the x-ray beam before the x-ray beam reaches the sample.